Reflections on Mismatches in the Fertility Preferences in Latin America - Angelita Alves de Carvalho; Gabriela Marise Bonifácio (Revista Latinoamericana de Población)
This study aims to estimate and analyze four selected indicators of contradictions in female fertility preferences, which are called mismatches. Therefore, we seek to analyze the responses to the questions that women are asked regarding their ideal number of children, their current number of children, their future fertility intentions, and their use of contraceptive methods. Data from demographic and reproductive health surveys from fourteen countries in Latin America between 2006 and 2017 were used. An estimated occurrence of mismatches of 11 % was observed for the countries studied, and cases in which women were classified with a negative discrepancy and said that they do not want more children in the future prevailed. It can be inferred that despite the existence of several inconsistencies, the responses of Latin American women to questions about their fertility preferences are robust and very predictive.